Insect Affects. A Study on the Motivations of Amateur Entomologists and Implications for Citizen Science - Santaoja Minna (The Finnish society for science and technology studies, 2022)
With increasing interest in citizen science, this paper discusses how amateur naturalism, especially amateur entomology, is placed within citizen science discourses. Through a case study of amateur entomology in Finland, the paper discusses amateurs’ diverse motivations for engaging with nature. The paper discusses especially the affective and ethical aspects of amateur entomology and its implications for citizen science. The discussion is based on an ethnographic study of an entomologist society. The paper suggests that amateur naturalism cannot be reduced to any single definition of citizen science, but amateur entomologists enact different epistemologies as knowledge producers and active citizens. The amateurs are often motivated by an ethical ‘first contract’ with nature. The rich amateur culture may democratize and ‘re-enchant’ science, provided the scientist worldview of superior data is not allowed to conceal the diversity of amateur motivations.